NAZ wallpaper productions: wallpaper tiles / Muhammad Zakwan Mushairry, Nasuha Ismail, Nik Nur Ayunie Nik Mohd Baharin Gurian - Mushairry, Muhammad Zakwan; Ismail, Nasuha; Nik Mohd Baharin Gurian, Nik Nur Ayunie (2017)
NAZ Wallpaper is a new company operated in Malaysia and managed by bumiputera. The name of this company comes out from nickname of all of our company members. It shows that how we positioning our products in customers mind until they can remembering our company's name, simple and easy to pronounce.